Oxytetracycline residue in Tilapia - Barman, AKA; Hossain, MM; Rahim, MM; Hassan, MT; Begum, M (Bangladesh Journal of Scientific and Industrial Research, 2018)
The present study was conducted to determine the persistence of oxytetracycline residue in Tilapia (Oreochromis niloticus) available in local fish markets of Sylhet Sadar Upazila. To carry out this experiment, 24 fish samples were randomly collected from four (4) local fish markets under study area from March 2016 to August 2016. Fish samples were analyzed by using High Performance Liquid Chromatography (HPLC) method to detect amount of residues of oxytetracycline. In this study, detectable oxytetracycline residues were observed in five (5) samples of Tilapia ranged between 23.77-39.94 ppb (mean 38.88±2.99 ppb). Oxytetracycline residues less than limit of detection were also found in 19 (79.17%) samples. The detected residues of oxytetracycline in these fish samples did not exceed the maximum residue limit (MRL) 100 ppb recommended by the European Commission. However, long term persistence of high level oxytetracyclines could be a potential hazardous for public health. For this reason supervision of antibiotic uses and monitoring of optimum MRL in Tilapia are utmost needed for farmed fish species. Bangladesh J. Sci. Ind. Res.53(1), 41-46, 2018